Change of Vegetation Cover at Rohingya Refugee Occupied Areas in Cox’s Bazar District of Bangladesh: Evidence from Remotely Sensed Data (Journal of Environmental Science and Natural Resources, 2019)
Nearly one million Rohingya Refugees are living in Cox’s Bazar—a south-eastern district of Bangladesh; among them, more than half a million have fled Myanmar since August 2017. There are always some impacts of refugee settlements on the host environment. Hence, this study has made an initiative to investigate the changes of vegetation covers in four refugee occupied Unions of Teknaf and Ukhia Upazila. Analysing the remotely sensed Landsat imageries using Normalized Difference Vegetation Index method, the spatial extent of sparse vegetation, moderate vegetation, and dense vegetation before and after the occurrence of 2017 Influx have been quantified. The result reveals that nearly 21,000 acres of dense vegetation and more than 1700 acres of moderate vegetation have been reduced within the period of one year in-between 2017 and 2018. On the other hand, during the same period, the refugee sites have been expanded by almost 6000 acres. The main reasons for this drastic reduction of vegetation include the construction of refugee camps by felling the forest and consumption of firewood by refugees from the surrounding forest of their camps. Arrangement of alternative cooking fuel, relocation of refugees, reforestation, and accelerating the repatriation process may reduce the further degradation of vegetation.J. Environ. Sci. & Natural Resources, 11(1-2): 9-16 2018